Володимир Коряк і його критика культури - Омельчук, О.Р. (Слово і Час, 2019)
У статті проаналізовано зміст і напрямки літературно-критичної діяльності Володимира Коряка
(1889 – 1937), яку визначала ідея пролетарської культури. Її головний принцип, сформульований
у філософії марксизму, полягав у протистоянні буржуазного і пролетарського світу. Доробок
критика відображає конфлікти і компроміси, яких зазнавала концепція української пролетарської
літератури впродовж 1919 – 1934 рр., свідчить про те, що в тогочасній пролетарсько-марксистській
критиці співіснували й постійно варіювалися три схеми конструювання пролетарської
літератури: пролетарська література як те, що твориться з нуля; пролетарська література
як продовження закладених у дожовтневому письменстві соціалістичних ідей; пролетарська
література як трансформація й рекомбінація минулих (буржуазних) рис у поєднанні з новими,
пролетарськими. According to the author of the article, the content and directions of literary criticism of Volodymyr
Koriak (1889–1937) were determined by the idea of proletarian culture. Its basic principle was the
struggle between the bourgeois and proletarian world, formulated in the philosophy of Marxism.
However, this concept was not sufficient to build the concept of Ukrainian proletarian literature. In
1920s the most problematic for the critics was the choice of the criteria for identifying the literary text
as a proletarian one. They had to take into account such non-textual factors as the author’s biography,
national cultural forms, historical influences of Europeanism, colonialism, anti-colonialism, nationalism,
imperialism, etc.
Koriak’s works reflect the conflicts and compromises that the concept of Ukrainian proletarian
literature underwent during 1919 – 1934. Especially complicated were such topics as the history of
Ukrainian Marxist-proletarian thought, the ‘Borotbyst’ narrative, the issues of proletarian style and
bourgeois cultural influences. The Ukrainian ‘narodnytstvo’ became a major part of Koriak’s critique.
As a result, the bourgeois legacy (namely modernism, ‘narodnytstvo’, ‘national literature’) in Koriak’s
literary-critical discourse received a particular negative evaluation.
Koriak’s literary work testifies to the fact that the proletarian-Marxist criticism of his contemporaries
is featured by the coexistence of the three schemes of constructing proletarian literature: proletarian
literature as terra nova; proletarian literature as a continuation of the socialist ideas of the pre-October
literary works; proletarian literature as a transformation of the past (bourgeois) qualities and their
recombination with new proletarian ones.